Reclaimed water reuse as a tool to reduce nutrient loads in the Baltic Sea - Krumins, Janis; Ramm, Klara; Purmalis, Oskars; Mezulis, Marcis; Klavins, Maris (Frontiers in Water, 2026)
Eutrophication is a critical environmental challenge in the Baltic Sea, driven predominantly by excessive inputs of nitrogen and phosphorus. While diffuse agricultural runoff constitutes the largest share of nutrient pollution, point sources, particularly municipal wastewater discharges, continue to contribute significantly in specific regions. This paper investigates the potential of reclaimed water reuse as a strategic measure to mitigate nutrient loads to the Baltic Sea. Reclaiming water from wastewater and utilizing it in agriculture, industry, and urban greening shows a potential opportunity for reducing direct nutrient discharges while conserving freshwater resources and decreasing dependency on synthetic fertilizers.